Self-introduced intravesical magnets in a 3-year-old boy: Case report - Özdemir, Tunç; Orhan, Gizem; Candan, Belce; Köylüoğlu, Gökhan (The Turkish Journal of Pediatrics, 2019)
Self-introduced intravesical foreign bodies are commonly seen in adults and are rarely encountered in children. The underlying cause may be a psychiatric disorder for sexual gratification or inquisitiveness as in children. We herein report a 3-year-old boy who was presented with pathological lower urinary tract symptoms and a radiopaque, irregular shaped object in bladder detected by direct abdominal radiograph. Preoperative diagnosis was bladder calculus. Cystolithotomy was planned via Pfannenstiel approach. During operation, self-introduced small magnets and a metallic bead which stuck together were detected. Intravesical foreign bodies are important considerations in the differential diagnosis of pathological lower urinary tract symptoms. In this case, magnets that were stuck together and a metallic bead mimicked bladder calculus radiologically. However, irregular shape of the intravesical object may arouse a suspicion about the nature.